Effect of Local Cooling and Blood Flow Restriction on Muscle Weakness and Atrophy Caused by Detraining - KUBOTA, ATSUSHI; SAKURABA, KEISHOKU; ENDO, SHINYA (Juntendo Iji Zasshi = Juntendo Medical Journal, 2016)
Objective: To prevent muscle weakness and atrophy that are caused by discontinuing sports activities, we investigated the effect of local cooling and blood flow restriction (BFR) during detraining. Methods: Eleven healthy men (23.8±2.1 years) performed elbow flexion resistance training three times per week for 6 weeks. After training, the subjects were instructed to limit the upper arm activity within their activities of daily living level during 3 weeks of detraining. During the detraining period, one arm was used as a control (CON, n=11); the other arm was used under the condition of cooling at medial side of upper arm by an ice bag (ICE, n=6), or under BFR (BFR, n=5). Measurements included elbow flexion torque at angular speeds of 60°/s and 120°/s under concentric contraction and isometric contraction (IM) and cross-sectional area of the upper arm. Measurements were conducted at pre-training (Pre); post-training (Post); and after 1week (W1), 2 weeks (W2) and 3 weeks (W3) of detraining. Results: IM torque and cross-sectional area significantly increased following training in all conditions. During detraining, IM torque significantly decreased under the CON condition (Post, 73.2±19.9 Nm; W3, 64.3±11.6 Nm), but no significant changes were observed under ICE condition. However, BFR condition significantly increased following detraining. The percent change in each condition during detraining was significant between the CON and BFR conditions at W2 and W3. Cross-sectional area significantly decreased following detraining in all conditions. Conclusions: Local cooling and BFR suppressed muscle weakness that was caused by detraining.